ASSESSMENT OF ANTIOXIDANT ACTIVITY OF IRAQI CAPPARIS SPINOSA L. FLOWER EXTRACT - Ali , Sarah Jamal; Hamad , Sumaya F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to explain the effect of the crude extract and the flavonoid extract of Capparis spinosa L flowers as an antioxidant in vitro and the effect of the flavonoid extract as an antioxidant in the tissues of kidney cells. Different concentrations(7.5, 15, 30, 60, 150, 300, 600) µg/ml of the two extracts were selected to determine the antioxidant activity in vitro by using DPPH 1,1 Dyphenyl-2-picrylhydrazyl radical. The results showed the efficiency of the flavonoid extract on the crude extract, and it was the highest at concentrations of 150, 300, and 600µg/ml, as it gave 100% compared with the crude extract, which gave 40%, 67%, 75% and for the same concentrations. The flavonoid extract was also used at a concentration of 50 mg per kg, to estimate the antioxidant activity on kidney tissues after the creation of free radicals ( reactive oxygen species ROS) inside them by mefenamic acid. The results showed that the used extract has an anti-oxidant effect. The flavonoid extract of the caper plant led to a statistically significant decrease in the concentration of malondialdehyde (MDA), in addition to a significant increase the level of glutathione (GSH). This study confirmed a possibility of using the flavonoid extract of the caper plant C. Spinosa in medical applications and in the treatment of different types of diseases caused by free radicals